The Effectiveness of Project Based Learning Integrated with Deep Learning in Improving Students' Creative Thinking Skills - Resma Wahyuni; Nursal Nursal; Irda Sayuti; Darmadi Darmadi; Mariani Natalina L; Nadia Ramona (FKIP - Universitas Riau, 2026)
Creative thinking is required in basic biology courses, however, students’ average creative thinking ability is still relatively low. This study uses a quasi-experimental research design of the posttest only control group model which aims to analyze the effectiveness of the deep learning integrated PjBL learning model to improve students' creative thinking skills in basic biology courses. The subjects of the study were the control class that produced poster products through conventional learning and the experimental class that produced video products through PjBL-Deep learning learning. Creative thinking skill data was obtained through product assessment using an assessment sheet with a likert scale of 1-4 based on 13 creative thinking indicators. The results showed that the percentage of creative thinking skills in the experimental class was in the very creative category while the control class was in the category of quite creative to creative. A statistical test using Mann-Whitney showed an Asymp value. Sig (2-Tailed) of 0.001 < 0.05 so that it was concluded that there was a significant influence of the application of the deep learning integrated PjBL model on the improvement of students' creative thinking skills in basic biology courses.